Exocrine pancreatic insufficiency following bariatric surgery: unveiling alternative aetiology—case report and short review - Milad, Camila; Nunez-Pizarro, Jorge Luis; Ibarzábal, Ainitze; Claro, María; Leyes, Pere; Vaquero, Eva; Moizé, Violeta; Jiménez, Amanda; Molero, Xavier; de Hollanda, Ana (European journal of clinical nutrition, 2023)
Bariatric surgery (BS) is currently the most effective treatment for severe obesity, requiring ongoing multidisciplinary follow-up to ensure proper progress and nutrition post-procedure. Despite its favourable safety profile, it is not exempt from complications, one of which being exocrine pancreatic insufficiency (EPI). The underlying pathophysiological mechanisms of EPI after BS are multifactorial, including poorly synchronized pancreatic enzyme secretion with the passage of nutrients (pancreaticocibal or postcibal asynchrony), insufficient pancreatic stimulation and bacterial overgrowth. We conducted a short literature review of the topic through a case of a patient who underwent BS in our centre and subsequently developed EPI and severe malnutrition. EPI initially was attributed to the surgery, but after a comprehensive evaluation, an unexpected cause was revealed.